Psychiatric emergency department visits during the coronavirus disease-2019 pandemic - Sun, HaiMing; Liu, HaiChun; Ma, ChunYan; Chen, Zheng; Wei, YanYan; Tang, XiaoChen; Xu, LiHua; Hu, YeGang; Xie, YuOu; Chen, Tao; Lu, Zheng; Wang, JiJun; et al. (Frontiers in Psychiatry, 2023)
Background Previous research has demonstrated the negative impact of the coronavirus disease-2019 (COVID-19) pandemic on mental health. Aims To examine changes in the Chinese psychiatric emergency department (PED) visits for mental health crises that occurred during the pandemic. Methods Before and during the COVID-19 pandemic, PED visit counts from the largest psychiatric hospital in China between 2018 and 2020 were investigated. Electronic medical records of 2020 PED visits were extracted during the COVID-19 pandemic period and compared for the same period of 2018 and 2019. Results Overall, PED visits per year increased from 1,767 in 2018 to 2210 (an increase of 25.1%) in 2019 and 2,648 (an increase of 49.9%) in 2020. Compared with 2 years before the epidemic, during the COVID-19 pandemic, the proportion of PED visits among patients with stress disorders, sleep disorders, and anxiety disorders increased significantly. In terms of the distribution of demographic characteristics, age shows a younger trend, while the gender difference is not significant. Conclusion These findings suggest that PED care-seeking increases during the COVID-19 pandemic, highlighting the need to integrate mental health services for patients with stress, sleep, anxiety, and obsessive-compulsive disorders during public health crises.